LKPD-Based Development Thematic Students of Grade II Elementary School - Zelmi Kaffa; Risda Amini (Universitas Pendidikan Indonesia (UPI), 2023)
This study aimed to produce products in the LKPD and analyze the effectiveness of LKPD thema of caring for animals and plants. The approach used in the research and development based on the model developed by Borg and Gall. The population in this research were the students at class two of elementary 30 Ps. Lakitan and elementary 24 Koto Raya. The collecting technique was done by using observation, interview, questionnaire and written test. And then the data were analized school and quantitatively and qualitatively. The last product of this research is LKPD already evaluated by master of matery , master of design and also limited test. Result of this research are: (1) Produced of work sheet to student, (2) the thematic material effective for studying looked from the result of study achieving standard maximum class.